Appropriateness of paediatric admission. Issue 1 (July 1994) - MacFaul, R; Glass, E J; Jones, S
Abstract : A study of the 'appropriateness' of 267 consecutive emergency admissions to a district paediatric department showed that admission was at a peak in the evening and night time. Breathing difficulty, head injury, and fever were the commonest presenting problems. Sixty three per cent of admissions occurred between 6 pm and 8 am and these were more likely to be after self referral to the accident and emergency department and were evenly distributed through the social classes. Overall 80.5% of admissions were considered to be necessary on medical grounds by the consultants at the time of discharge. Parental assessment of severity of illness and need for admission correlated well with that of the doctors. Fifty two per cent of all admissions took place though the accident and emergency department, and although a higher number of these were from disadvantaged families these were equally appropriate on medical grounds to those sent for admission by the general practitioner. Altogether 26.5% of admissions were for less than 24 hours and half of these were judged to be unnecessary. Implications for the organisation of inpatient care are discussed.